2022
DOI: 10.1038/s41467-022-33792-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-COV-2 antibody responses to AZD1222 vaccination in West Africa

Abstract: Real-world data on vaccine-elicited neutralising antibody responses for two-dose AZD1222 in African populations are limited. We assessed baseline SARS-CoV-2 seroprevalence and levels of protective neutralizing antibodies prior to vaccination rollout using binding antibodies analysis coupled with pseudotyped virus neutralisation assays in two cohorts from West Africa: Nigerian healthcare workers (n = 140) and a Ghanaian community cohort (n = 527) pre and post vaccination. We found 44 and 28% of pre-vaccination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 45 publications
6
18
0
Order By: Relevance
“…26 Other studies in Africa also measured higher SARS-CoV-2 seroprevalence among vaccinated participants, higher neutralizing antibody titers among participants with infection and vaccination, and faster waning of antibodies post-vaccination among participants who had not been infected. 7,[27][28][29] These results support the recommendation for COVID-19 vaccination (including booster doses) regardless of past infection. COVID-19 vaccination campaigns were conducted throughout Zambia during the study period, but vaccine coverage among study participants was lower than the general population, possibly reflecting hesitancy toward vaccination during pregnancy, and only about 12% of the fully vaccinated population has received a booster dose.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…26 Other studies in Africa also measured higher SARS-CoV-2 seroprevalence among vaccinated participants, higher neutralizing antibody titers among participants with infection and vaccination, and faster waning of antibodies post-vaccination among participants who had not been infected. 7,[27][28][29] These results support the recommendation for COVID-19 vaccination (including booster doses) regardless of past infection. COVID-19 vaccination campaigns were conducted throughout Zambia during the study period, but vaccine coverage among study participants was lower than the general population, possibly reflecting hesitancy toward vaccination during pregnancy, and only about 12% of the fully vaccinated population has received a booster dose.…”
Section: Discussionsupporting
confidence: 74%
“…Antenatal care (ANC) clinics have been utilized in several countries in Africa to monitor SARS-CoV-2 seroprevalence in a healthy population of women accessing healthcare services. [5][6][7][8][9] In Ethiopia, SARS-CoV-2 surveillance conducted in ANC clinics between April 2020 and March 2021 first detected SARS-CoV-2 antibodies in June 2020 and peaked at 11.8% in February 2021. 10 Repeated cross-sectional serosurveys in ANC clinics in Kenya found that most women were seropositive for SARS-CoV-2 antibodies by October 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Others have used varied methods to differentiate reinfection from initial infection ( 40 , 41 ). One macaque study showed a 7.6-fold rise in N-IgG antibody as indicative of reinfection ( 21 ), while a human West Africa study suggested a 7-fold rise ( 20 ); similar titre rises were also observed in studies from high-income settings ( 42 , 43 ). Our serological data from two SARS-CoV-2 reinfected patients with rt-PCR confirmation showed an 11-fold rise in N-IgG antibody concentration after reinfection.…”
Section: Methodsmentioning
confidence: 76%
“…Accordingly, antibodies directed against the S protein, particularly the RBD, are critical targets for developing vaccines and therapeutics (13)(14)(15) due to their positive associations with viral neutralisation titres (16)(17)(18)(19). On the other hand, the Nucleoprotein serves as the primary target in many serosurveillance test systems, and serological responses to N infer prior SARS-CoV-2 exposure (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The antigenic shift represented by Omicron (B.1.1.529) resulted in a radically different virus characterized by multiple mutations in spike with extreme immune evasion of vaccines and increased transmissibility. [6][7][8][9][10][11][12][13] Immunological imprinting or original antigenic sin (OAS) 14 refers to a phenomenon where primary exposure to a pathogen shapes future immune responses to related strains [14][15][16] . As more antigenically distinct variants evolve, imprinting of the primary infection strain may limit the potency and breadth of humoral responses, instead favouring antibodies binding conserved epitopes.…”
Section: Introductionmentioning
confidence: 99%